A modeling method of sport shoes for dynamic analysis of shoe-body coupled system - Koike, S.; Okina, S. (Procedia Engineering, 2012)
The purpose of this study was to quantify the functional role of compressive characteristics of shoe sole by combining a finite-truss-element shoe sole model and the equation of whole-body motion. The equation of the shoe sole deformation was developed by modeling shoe sole as a construction of truss elements that have nonlinear spring and damper. The properties of the spring and damper were identified from impact test by using an impact device containing an accelerometer and an arm with impactor. The equation of whole-body motion was derived by modeling the human body as a system of 15-rigid linked segments. Dynamic contributions of the support leg joint torques, which were caused by the elastic and viscous forces on the shoe sole, to the generation of whole-body CG's acceleration were calculated under constant running speed condition. A fore/mid foot contact type runner participated as subject. The results in this study indicate that 1) the ankle joint torque caused by the elastic property of the forepart of shoes sole contributes to the acceleration of whole-body CG, and 2) the knee joint torque caused by the viscous property of shoe sole shows negative contribution to the body support but shows positive contribution to the propulsion.